2021
DOI: 10.3390/cli9030043
|View full text |Cite
|
Sign up to set email alerts
|

Synoptic Climatology of Lake-Effect Snow Events off the Western Great Lakes

Abstract: As the mesoscale dynamics of lake-effect snow (LES) are becoming better understood, recent and ongoing research is beginning to focus on the large-scale environments conducive to LES. Synoptic-scale composites are constructed for Lake Michigan and Lake Superior LES events by employing an LES case repository for these regions within the U.S. North American Regional Reanalysis (NARR) data for each LES event were used to construct synoptic maps of dominant LES patterns for each lake. These maps were formulated us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 45 publications
2
15
0
1
Order By: Relevance
“…[20]) form during LES events. This was observed in [35] and [36] who found that, for a PBL thermodynamic profile conducive to LES formation, subtle variations in the surface dipole structure driven by deviations in the synoptic scale pattern led to varying LES snow band types and impacts.…”
Section: Introductionmentioning
confidence: 79%
See 4 more Smart Citations
“…[20]) form during LES events. This was observed in [35] and [36] who found that, for a PBL thermodynamic profile conducive to LES formation, subtle variations in the surface dipole structure driven by deviations in the synoptic scale pattern led to varying LES snow band types and impacts.…”
Section: Introductionmentioning
confidence: 79%
“…Additionally, as the clipper propagates and matures, an anticyclone will typically build in its wake which creates a pressure dipole and tight isobaric gradient between the two pressure systems. As [35,36] note, in addition to strong flow, this dipole has also been linked with LES off the Great Lakes.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations